Efektivitas Program Kios Pelayanan Administrasi Kependudukan Langsung Jadi di Kelurahan Gempeng Kecamatan Bangil Kabupaten Pasuruan - Rokhmawati, Desi Nur; Widiyarta, Agus (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Population administration services in their implementation there are still many complaints from the public. So that all local governments are encouraged to change the image of public services through innovation. The Department of Population and Civil Registration of Pasuruan Regency has an innovation in realizing the acceleration of the quality of public services, namely by launching the Direct Population Administration Service Kiosk program (Kios e-PAKLADI), a program by opening population administration service kiosks at the village/kelurahan level. This program has been able to overcome geographical constraints caused by the distance between residents and service locations. The purpose of this study was to describe and analyze the effectiveness of the instant population administration service kiosk program (Kios e-PAKLADI) in Gempeng Village, Bangil District, Pasuruan Regency. This study uses a qualitative descriptive research method with data collection techniques of observation, interviews, and documentation. Data analysis techniques namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Direct Population Administration Service Kiosk program (Kios e-PAKLADI) in Gempeng Village has been effective but not optimal. Judging from the indicators of resources, funds, facilities and infrastructure that have been used effectively but not optimal, that is, there are still facilities and infrastructure that have not been fulfilled. The number and quality of services produced have been effective. The time limit for producing goods or services is effective but not optimal, namely there is service time that is not in accordance with predetermined standard operating procedures. And the procedures that must be carried out are effective.